The Cost-Effectiveness of Falls Prevention Interventions for Older Community-Dwelling Australians - Church, J.; Goodall, S.; Norman, Richard; Haas, M. (Blackwell Publishing, 2012)
Objective: To evaluate the cost-effectiveness of strategies designed to prevent falls among older people. Methods: A decision analytic Markov model of interventions designed to prevent falls was developed. Incremental cost-effectiveness ratios (ICERs) using quality adjusted life year (QALYs) as the measure, were calculated for those interventions aimed at the general population (home exercise, group exercise, tai chi, multiple and multi-factorial interventions); high-risk populations (group exercise, home hazard assessment/modification and multi-factorial interventions); and specific populations (cardiac pacing, expedited cataract surgery and psychotropic medication withdrawal). Uncertainty was explored using univariate and probabilistic sensitivity analysis. Conclusion: In the general population, compared with no intervention the ICERs were tai chi ($44,205), group-based exercise ($70,834), multiple interventions ($72,306), home exercise ($93,432), multifactorial interventions with only referral ($125,868) and multifactorial interventions with an active component ($165,841). The interventions were ranked by cost in order to exclude dominated interventions (more costly, less effective) and extendedly dominated interventions (where an intervention is more costly and less effective than a combination of two other interventions). Tai chi remained the only cost-effective intervention for the general population. Implications: Interventions designed to prevent falls in older adults living in the community can be cost-effective. However, there is uncertainty around some of the model parameters which require further investigation.